Analisa Dampak UU Ciptaker (Penghapusan Minimal 30% Kawasan Hutan) Terhadap Perlindungan Dan Pengelolaan Konservasi Lingkungan Kawasan Hutan Gunung Lawu Kabupaten Karanganyar Dalam Perspektif Hukum Indonesia - Gusfani, Salsabila Hema; Hermawan, Sapto; Nugroho, Asianto (Faculty of Law Universitas Sebelas Maret Surakarta, 2024)
The aim of this research is to determine the implications of eliminating the minimum threshold of 30% of forest areas in river basins and islands to ensure environmental protection and management in the Gunung Lawu forest area, Karanganyar Regency from an Indonesian legal perspective. and the impact that will have on the protection and management of environmental preservation in the Mount Lawu forest area, Karanganyar Regency. This research is normative where the author will analyze and study it using relevant laws to find the necessary solutions.The results of his research, according to historical chronology, the figure of 30 percent was the doctrinal practice of the Dutch East Indies government. So the specifications are less relevant to the current implementation. If this consolidated Omnibus Law is implemented, then Article 18 of the Forestry Law which regulates a minimum of 30 percent of forest area will no longer apply.. This elimination aims to remove obstacles in areas where the forest area is less than 30% so that development can continue, such as in other forest areas which still have a forest area of more than 30%. Opportunities for increasing conservation and environmental management in the Mount Lawu forest area, Karanganyar Regency can be made into National Park status. National Parks are natural conservation areas that have original ecosystems, managed using a zoning system that are used for scientific research, education, cultivation support, tourism and natural recreation.